Analisis Pemahaman Mahasiswa Terhadap Pernyataan Akuntansi Syariah Dalam Pembiayaan Mudharabah - Yuni Novalini Rahayu Siregar; Nana Diana (Peneliti.net, 2023)
This study aims to determine understanding and differences understanding of accounting study program students towards financing accounting mudharabah and musyarakah in the Faculty of Business Economics. Namely a study on students concentrating on Islamic accounting, this research carried out at the Faculty of Economics & Business UNSIKA. The type of research used in this research is descriptive quantitative, the population and sample are Accounting students and sharia accounting concentration, the data used in this study is primary data, there are data collection techniques namely by distributing questionnaires to students concentration sharia accounting as a research respondent. And using the SPSS tool as a data processing tool or value analysis of the respondents. Research result shows that there is no difference in understanding between accounting Mudharabah and musyrakah financing, namely with various existing criteria sufficient, insufficient and sufficient, but not available differences in understanding between male students and female students regarding mudharabah financing accounting.